Blood-Brain Barrier Permeability Study In Multiple Sclerosis - ChernenkoМ. E. (Psychiatry, Neurology and Medical Psychology, 2016)
Blood-brain barrier is an important factor in determining the specificity of the central nervous system lesions in multiple sclerosis. In the article were described the features of functioning of the blood-brain barrier in multiple sclerosis (MS). The data of complex examination of 135 patients with different types of MS, which have been applied clinical and paraclinical methods with evaluation of reliability of the results. The study identified particular changes in permeability of the blood brain barrier at different types of the disease at different stages of the pathological тprocess, that had great practical importance. Practical recommendations were formulated.